Determination of gaseous and particulate carbonyls (glycolaldehyde, hydroxyacetone, glyoxal, methylglyoxal, nonanal and decanal) in the atmosphere at Mt. Tai - K. Kawamura (Atmospheric Chemistry and Physics, 2013)
Gaseous and particulate semi-volatile carbonyl compounds were determined every three hours in the atmosphere of Mount Tai (elevation, 1534 m) in the North China Plain during 2–5, 23–24 and 25 June 2006 under clear sky conditions. Using a two-step filter cartridge in a series, particulate carbonyls were first collected on a quartz filter and then gaseous carbonyls were collected on a quartz filter impregnated with O-benzylhydroxylamine (BHA). After the two-step derivatization with BHA and N,O-Bis(trimethylsilyl)trifluoroacetamide (BSTFA), carbonyl derivatives were measured using a gas chromatography. The gaseous concentrations were obtained as follow: glycolaldehyde (range 0–826 ng m−3, average 303 ng m−3), hydroxyacetone (0–579 ng m−3, 126 ng m−3), glyoxal (46–1200 ng m−3, 487 ng m−3), methylglyoxal (88–2690 ng m−3, 967 ng m−3), n-nonanal (0–500 ng m−3, 89 ng m−3), and n-decanal (0–230 ng m−3, 39 ng m−3). These concentrations are among the highest ever reported in the urban and forest atmosphere. We found that gaseous α-dicarbonyls (glyoxal and methylglyoxal) are more than 20 times more abundant than particulate carbonyls and that glycolaldehyde is one order of magnitude more abundant than in aerosol phase. In contrast, hydroxyacetone and normal aldehydes (nonanal and decanal) are equally present in both phases. Time-resolved variations of carbonyls did not show any a clear diurnal pattern, except for hydroxyacetone. We found that glyoxal, methylglyoxal and glycolaldehyde positively correlated with levoglucosan (a tracer of biomass burning), suggesting that a contribution from field burning of agricultural wastes (wheat crops) is significant for the bifunctional carbonyls in the atmosphere of Mt. Tai. Upward transport of the pollutants to the mountaintop from the low lands in the North China Plain is a major process to control the distributions of carbonyls in the upper atmosphere over Mt. Tai.